Genetic manipulation of Escherichia coli central carbon metabolism for efficient production of fumaric acid. (December 2018) - Liu, Huan; Song, Ruirui; Liang, Yue; Zhang, Ting; Deng, Li; Wang, Fang; Tan, Tianwei
Highlights: The effect of the glucose uptake system on the production of fumaric acid was studied. The malic acid metabolic way was inhibited to increase fumaric acid production. A new metabolic pathway was constructed to increase the conversion of acetic acid. The production of fumaric acid increased by 50% in comparison with the original strain. Abstract: Fumaric acid is one of the top 12-biomass building-block chemicals. In this study, we reported manipulation of E. coli central carbon metabolism with the aim to decrease the by-products and improve fumaric acid production. PEP-dependent glucose phosphotransferase system was replaced with a galactose translocation system to minimize the consumption of phosphoenolpyruvate. Engineering anaplerotic pathway (phosphoenolpyruvate carboxylase) was employed to redistribute carbon flux from glycolysis to Krebs cycle. Deletion of malate dehydrogenase and overexpression of acetyl-CoA synthase could decrease the byproducts malic acid and acetic acid. The combined strategies led to fumaric acid yield up to 1.53 g/g dry cell weight, a 50% increase compared with the parental strain. The result demonstrated that these genetic modifications were effective strategies for improving the production of fumaric acid and the engineered strain may serve a platform microbial cell factory for efficient production of fumaric acid or other dicarboxylic acids.